2018
DOI: 10.3390/jcm7090256
|View full text |Cite
|
Sign up to set email alerts
|

The Thomsen-Friedenreich Antigen: A Highly Sensitive and Specific Predictor of Microsatellite Instability in Gastric Cancer

Abstract: Microsatellite instability (MSI) is a distinct molecular subtype of gastric cancer. In recent years, the clinical consequences of MSI and the therapeutic opportunities to target this peculiar cancer subtype became evident. However, despite the importance of MSI for the stratification of patients, the time and resources required for diagnosis still present an obstacle. In an attempt to identify a new marker for MSI in gastric cancer, we evaluated the expression of five cancer-associated glycan epitopes in a coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
(34 reference statements)
0
19
1
Order By: Relevance
“…Therefore, it is likely the lack of complex O-glycosylation due to core 1 O-glycan loss is affecting events at the mucosal surface (where Muc5AC is expressed). Importantly, both glycan truncation and alterations such as αGlcNAc deficiency are reported in gastric cancer (David et al, 1992; Duarte et al, 2016; Li et al, 2018; Mereiter et al, 2018; Springer, 1984; Werther et al, 1994), highlighting the diverse means by which O-glycans and their alterations contribute to gastric homeostasis and disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is likely the lack of complex O-glycosylation due to core 1 O-glycan loss is affecting events at the mucosal surface (where Muc5AC is expressed). Importantly, both glycan truncation and alterations such as αGlcNAc deficiency are reported in gastric cancer (David et al, 1992; Duarte et al, 2016; Li et al, 2018; Mereiter et al, 2018; Springer, 1984; Werther et al, 1994), highlighting the diverse means by which O-glycans and their alterations contribute to gastric homeostasis and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although aberrant glycosylation, including loss of complex O-glycans, occurs in patients with gastric cancer (Fu et al, 2016; Mereiter et al, 2018), its exposure level in human gastritis remains unclear. It was shown that Tn-antigen exposure did not change relative to disease status in a patient cohort, being limited to the supranuclear (Golgi-localized region; Barresi et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant glycosylation on the cell surface is considered a hallmark of cancer with potential applications in the clinical setting [16]. In this regard, GC has been shown to express simple O-glycan antigens [19], and recently an association between the expression of the glycan antigen Thomsen-Friedenreich (TF) and the MSI status of GC tumors has been described, highlighting this glycan antigen as a biomarker with potential consequences for patient stratification [40].…”
Section: Discussionmentioning
confidence: 99%
“…52 For instance, we observed low antibody reactivity to TACAs known to be expressed on CVID-associated malignancies, such as GM1 in non-Hodgkin lymphoma 37 or Thomson-Friedenreich antigen in gastric cancer. 53,54 However, tumor glycosylation patterns and their immunoreactivity remain to be fully explored for CVID-associated malignancies.…”
Section: Discussionmentioning
confidence: 99%